PENERAPAN MEDIA PEMBELAJARAN BERBASIS MOBILE LEARNING DI SMP NEGERI 4 ABUNG BARAT - Kurnia, Ulfa Isni; Lathifah, Afra; Rizki, Fahlul; Larasati, Bayu Sekar; Sari, Selly Puspita (Jurnal Pengabdian Kepada Masyarakat Ungu( ABDI KE UNGU), 2024)
The use of mobile learning-based learning media technology in junior high schools (SMP) has become a major highlight in the modern education era. However, there are still many members of society who experience limited access to digital education. In an effort to increase the level of digital literacy among the community, we have initiated a community service activity by utilizing mobile learning-based learning media technology. We use learning media that can be accessed via mobile devices commonly used by the public, such as smartphones. This activity has great potential to provide a significant positive impact, namely increasing students' abilities. The use of mobile learning-based learning media technology can expand the range of access to learning materials, increase the level of student involvement, and facilitate the learning process. The implications arising from this activity highlight the importance of integrating technology in the world of education to create a learning experience that is more dynamic and in line with the needs of the times. For educators, implementing mobile learning-based learning media technology requires a deep understanding of the potential and challenges involved, as well as a commitment to continuing to develop skills and knowledge in utilizing technology in an educational context.